Mapping Marketing Communication Using Digital Media - Muflihah, Euis; Fadhillah, Jihan; Setiawan, Adi (International Journal of Engineering, Science and Information Technology, 2025)
Digital marketing communications mapping involves analyzing marketing messages spread across various digital platforms. To gain a better understanding of customer behavior. The purpose of this research is to identify articles that examine the role of marketing communication mapping products using digital media and provide an understanding of mapping marketing as a creative approach to marketing. Additionally, this research seeks to present and explain mapping studies relevant to the theme. Similarity Visualization (Vosviewers) is an application used in this study to combine qualitative methodologies with bibliometric techniques. In order to find articles through Publish or Perish, users entered keywords like search engine marketing, influencers, affiliates, advantages, disadvantages, display advertising, customers, social media, digital media, and digital channels. A total of 604 articles were found, which VosViewer then processed. The analysis results suggest that scientific mapping and the potential for further research on mapping marketing could serve as reference variables for future academics in their articles.